Cervical Hyperostosis Leading to Dyspnea, Aspiration and Dysphagia: Strategies to Improve Patient Management - Psychogios, Georgios; Jering, Monika; Zenk, Johannes (Frontiers in Surgery, 2018)
Diffuse idiopathic skeletal hyperostosis (DISH) is a rare but well known cause of dysphagia. In very few cases aspiration and dyspnea are described as a clinical manifestation. An 82-year-old man presented himself in our clinic with severe dyspnea, aspiration, and pneumonia. After performing a microlaryngoscopy an emergency tracheotomy became necessary. In laryngoscopy a severe bulging of the posterior oropharyngeal and hypopharyngeal wall was detected. The glottis area was not observable and immobilisation of the right vocal cord could be detected. The CT showed anterior osteophytes and ossification of the anterior longitudinal ligament from C2–C7. We performed a panendoscopy in order to explore the upper aerodigestive area. Postoperatively an emergency tracheotomy was needed due to the development of laryngeal edema. The osteophytes were removed in cooperation with the department of orthopaedics. Three months postoperative the patient had no dyspnea or dysphagia, so the tracheotomy could be closed. Cervical hyperostosis is commonly described in elderly patients and usually presenting without symptoms, therefore a surgical treatment is usually not necessary. Nevertheless it can lead to severe morbidity and dyspnea with airway obstruction. Therefore it is essential that cervical hyperostosis is recognized early enough and appropriate treatment is initiated. Flexible endoscopy should be preferred over direct panendoscopy because it could lead to life-threatening edema and a prophylactic tracheostomy should be strongly considered in patients that present with severe dyspnea,